Enhancing EFL Education: The Role of Metadiscourse in Language Assessment - Entika Fani Prastikawati; Moses Adeleke Adeoye (Journal of Education Reseach and Evaluation, 2024)
This study was motivated by students' low ability to write and communicate effectively in English. This study aims to analyze the effect of metadiscourse on language assessment in the context of EFL (English as a Foreign Language) education. This study is a qualitative research. The subjects involved in the study were students learning English as a foreign language. The data collection method was through a robust literature review to establish basic knowledge of metadiscourse and its significance in language assessment. The review also included important works on metadiscourse language evaluation theory and research investigating the relationship between metadiscourse and language skills proficiency. Using a comparative perspective, the analysis of data from language assessment utilizes pass-linguistic and pass-cultural insights to complement the knowledge of metadiscourse in EFL education. By analyzing how metadiscourse operates in specific languages and cultural contexts, the researchers found widespread patterns in addition to particular language variations in the use of metadiscourse. The results showed that metadiscourse plays an important role in shaping students' language skills ability, discourse competence, and universal communicative effectiveness. In conclusion, integrating metadiscourse in language evaluation provides great hope for improving EFL training and promoting stronger language consequences.